Menulis Diary Sebagai Teknik Meningkatkan Kepercayaan Diri Pada Anak - Fadhilla Triayu; Randa Putra Kasea Sinaga (Yayasan Literasi Sains Indonesia, 2022)
Having a closed nature has many adventages such as being able to be a good listener, and doing more actions than talking. Not only does it have adventages, it also has some disadvantages, such as being difficult to communicate with, not having many friends, and being difficult to socialize with the surrounding environment. Some of these losses can cause a person to experience loneliness and withdraw from the social environment. If this happens continuosly it will have serious consequences. As a result, it can occur gradually, namely feeling insecure, and depressed. This also happened to one of the children at the Puteri Aisyiyah Orphanage who needed help to increase her confidence.The process of providing assistance was carried out in the PKL 1 mini project activity, namely by using the casework method. Several stages consist of Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and Termination. The focus of solving client problems is by writing a diary as a strategy to be used for clients to know who they are and their strengths in order to increase their confidence. The purpose of this strategy was declared successful with significant client changes, including opening up to those closest to them.